Mortality risk associated with blood sugar levels in patients with septicemia in Intensive Care - Adriana Cristina Moreira; Luciano Garcia Lourenção; Natália Sperli Geraldes Marin Santos Sassaki; Claudia Eli Gazetta; Silvia Helena Figueiredo Vendramini; Maria de Lourdes Sperli Geraldes Santos (Universidade Federal do Ceará, 2016)
Objective: to estimate the mortality risk associated with blood sugar levels in patients with septicemia in an Intensive Care Unit. Methods: this is a retrospective cohort study, performed with 263 patients with septicemia admitted to an intensive care unit, using the hospital management system data. Results: there was a higher frequency of patients aged from 14 to 59 years old (52.1%), male (55.9%), white (85.9%) of clinical specialties (65.8%); the hospitalization period ranged from 2 to 132 days; 91.6% of patients (n=241) were hyperglycemic at the time of hospitalization. There were 37 (14.1%) deaths, more frequent in patients with hyperglycemia during hospitalization (1.49 deaths/1,000 patients). Conclusion: hyperglycemia was a risk factor for mortality in patients admitted to the Intensive Care Unit.